The complete handbook of coaching - Cox, Elaine, Ed; Bachkirova, Tatiana, Ed; Clutterbuck, David, Ed (Sage Publications Ltd., 2014)
Provides the most comprehensive guide to the field of coaching, exploring a range of coaching theories and approaches, genres and settings, and professional issues. It supports trainees and professionals to identify and develop a personal style of coaching.